Channel Characteristics of Rail Traffic Tunnel Scenarios Based on Ray-Tracing Simulator. (1st August 2018) - Zhao, Jinmeng; Xiong, Lei; He, Danping; Du, Jiadong
Abstract : The tunnel scenario is a major rail communication scenario. In this paper, the radio channel characteristics of tunnel scenarios with different carrier frequencies, different distances between the transmitter (Tx) and receiver (Rx), and cross sections are simulated with a ray-tracing tool. Key parameters such as path loss, Rician K-factor, root mean square (RMS) delay spread, and angular spread are studied. According to the results, higher frequencies introduce larger path loss and the presence of the vehicle body increases the path loss by about 35 dB in the scenario; at the same time it will also cause the fluctuation and instability of the path loss. Besides, the influence of reflections from the side walls is significant on radio propagation. The channel experiences more severe fading in a narrow tunnel compared with others.